A facile and highly sensitive resonance Rayleigh scattering-energy transfer method for urea using a fullerene probe. Issue 51 (14th August 2018) - Yao, Dongmei; He, Zining; Wen, Guiqing; Liang, Aihui; Jiang, Zhiliang
Abstract : Under ultrasound conditions, a deep yellow fullerene (C60 ) colloid was prepared, which exhibits two resonance Rayleigh scattering peaks at 385 nm and 530 nm. Abstract : Under ultrasound conditions, a deep yellow fullerene (C60 ) colloid was prepared, which exhibits two resonance Rayleigh scattering peaks at 385 nm and 530 nm. Urea was reacted with dimethylglyoxime (DMG) to produce 4, 5-dimethyl-2-imidazole ketone (DIK), in the presence of stabilizer thiosemicarbazone (TSC). Resonance Rayleigh scattering energy transfer (RRS-ET) was shown to occur between the donor fullerene and acceptor DIK due to an overlap of the DIK absorption and fullerene RRS peaks. Upon an increase in the urea concentration, the RRS-ET was enhanced and the RRS intensity decreased. The decreased RRS intensity was linear to the urea concentration in the range of 6.66–333.00 nmoL L −1, with a detection limit of 2.0 nmoL L −1 . Accordingly, a new and simple RRS-ET method was established for detecting trace levels of urea in foods, with satisfactory results.